2020
DOI: 10.3390/molecules25214960
|View full text |Cite
|
Sign up to set email alerts
|

Wine or Beer? Comparison, Changes and Improvement of Polyphenolic Compounds during Technological Phases

Abstract: Wine and beer are nowadays the most popular alcoholic beverages, and the benefits of their moderate consumption have been extensively supported by the scientific community. The main source of wine and beer’s antioxidant behavior are the phenolic substances. Phenolic compounds in wine and beer also influence final product quality, in terms of color, flavor, fragrance, stability, and clarity. Change in the quantity and quality of phenolic compounds in wine and beer depends on many parameters, beginning with the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
34
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(36 citation statements)
references
References 244 publications
(363 reference statements)
1
34
0
1
Order By: Relevance
“…We discovered a higher risk of spirits for COVID-19. Sanja Radonjić et al have reported the differences between wine and beer in the presence and the concentrations of phenolic substances (32). They found that chalcones and flavanones were found only in beer, whereas other polyphenol classes (e.g., stilbenes, proanthocyanidins, and resveratrol) are found mainly in wine and champagne.…”
Section: Discussionmentioning
confidence: 99%
“…We discovered a higher risk of spirits for COVID-19. Sanja Radonjić et al have reported the differences between wine and beer in the presence and the concentrations of phenolic substances (32). They found that chalcones and flavanones were found only in beer, whereas other polyphenol classes (e.g., stilbenes, proanthocyanidins, and resveratrol) are found mainly in wine and champagne.…”
Section: Discussionmentioning
confidence: 99%
“…It is known that quercetin also belongs to the class of antioxidants and prevents oxidation reactions in those biological systems where it is present [62]. Being involved in the processes of oxygen capture in the presence of yeast cells decreases its quantity [48], but this leads to an intensification of microbial metabolism, which leads to a greater accumulation of secondary fermentation products that indirectly affect all organic compounds of beer, including melanoidins, catechins, caramels, and others, leading to color index changes [46,47,65]. On the other hand, nitrogen molecules present in the system bind to molecules of phenolic compounds, which leads to their enlargement and subsidence [26,33,49,51].…”
Section: Discussionmentioning
confidence: 99%
“…Phenolic acids usually have two different parent skeletons: hydroxycinnamic acid and hydroxybenzoic acid [ 19 , 155 ]. Among them, gallic acid is considered the most important phenolic acid because it is the precursor of all hydrolysable tannins [ 156 ].…”
Section: Non-flavonoidsmentioning
confidence: 99%